(3JQJjH GdCge eeG Mci ef WHbGJ GdSHcis - (3CMeO Hf YHO Gddg GdSGfIs
(3ChdgG (B:s
(3GdMeO ddg QGaY HYV GdfGS ahb HYV OQLGJ , hLGYd YdeGA cd CeI ai GdaVd WHbGJ s
(3BNQgG (B:s
(3BNQg ef JQLeI eMe Hf Nda Hf cGed TeS GdOjf GdZRi (B: (3hcGf ef JdGhI GdbQBf hcKQI GdJYHO hbjGe Gddjd hSdGeI GdUOQ hYOe GdENJdGW HGdOfjG HecGf heGJ QMeg Gddg HOeTb SfI (B770 [ (3hHYO Pdc JQLeI YHO GdMejO Hf GdLHdhi UGMH (B" (3GdHMQ GdUZjQ (B" (3hPcQ Cf Gds
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdJRe GdeDda efgL GdSHci ef MjK GdWHbGJ (B_ (3dcd eGFI SfI WHbI (B- (3dcfI QJH GdeJQLejf HMSH JGQjN hajGJge Ohf GdfXQ Edi GdJQJjH GdgLGFi Ke GNJUQ HYV GSJWQGOGJ GdSHci ai GdJQLeIs
(3hRGO HYV GdRjGOGJ CKfGA GdJQGLes
(3Ke JQLe ai Chd GdcJGH ddEeGe GdTGaYi QVi Gs
(3GdfSNI HgG MhGT s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg GdTjN CMeO Hf eMeO GdSGdei GdNGUg s
Keywords: (3GdJGQjNs